Energy, exergy, economic and environmental (4E) analysis of using city gate station (CGS) heater waste for power and hydrogen production: A comparative study. (18th January 2018) - Ghaebi, Hadi; Farhang, Behzad; Rostamzadeh, Hadi; Parikhani, Towhid
Abstract: This paper deals with energy, exergy, economic, and environmental (4E) analysis of two new combined systems for simultaneous power and hydrogen production. The combined systems are integrated from a city gate station (CGS) system, a Rankine cycle (RC), an absorption power cycle (APC), and a proton exchange membrane (PEM) electrolyzer. Since the pressure of natural gas (NG) in transmission pipeline is high, this pressure is reduced at CGS to a lower pressure. However, this NG has also ample potential to be recovered for multiple productions, too. In the proposed systems, the outlet energy of NG is used for power and hydrogen production by employing RC/APC and PEM electrolyzer. The power sub-cycles are driven by waste heat of CGS, while PEM electrolyzer is driven by this waste heat along with a portion of CGS-Turbine output power. A comprehensive thermodynamic modeling and parametric study of the proposed combined systems are conducted from the 4E analysis viewpoint. The results of two proposed systems are compared with each other, considering a fixed value of 1 MW for RC- and APC-Turbines power. Under the same external conditions and using steam as working fluid of RC, the thermal efficiency of the combined CGS/PEM-RC and -APC systems are obtained 32.9% and 33.6%, respectively. The overall exergy efficiency of the combined CGS/PEM-RC and -APC systems are also calculated by 47.9% and 48.9%, respectively. Moreover, the total sum unit cost of product (SUCP) and CO2 emission penalty cost rate are obtained 36.9 $/GJ and 0.033 $/yr for the combined CGS/PEM-RC and 36 $/GJ and 0.211 $/yr for the combined CGS/PEM-APC systems, respectively. The results of exergy analysis also revealed that the vapor generator (in both systems) has the main contribution in the overall exergy destruction. Highlights: To use waste heat of CGS for RC and APC for power production purposes. To replace the throttling valve of CGS by CGS-turbine and utilize specific portion of its power for hydrogen production. To analyze and compare two proposed systems based on the energy, exergy, economic, and environmental (4E) viewpoints. To present a comprehensive parametric study of some key elements on the main overall performance criteria of systems.